Impact of the war in Ukraine on the real estate market in Romania: Analysis in geopolitical context - Cristina Gabriela Cosmulese; Artur Zhavoronok (Geopolitics under Globalization)
The war in Ukraine has caused profound transformations in the dynamics of the Romanian real estate market, reflecting the impact of a complex combination of economic and financial, demographic and socio-cultural, as well as political and legal factors. In this context, the objective of the study is to analyze the impact of the war in Ukraine on the real estate market in Romania by assessing the influence of determinants to identify measures to support the stability and development of the real estate market within geopolitical crises. Subsequently, based on statistical analysis methods, the econometric model was developed considering as dependent variables the real estate market (measured by average price for housing) and independent variables – the number of Ukrainian migrants, interest rate on mortgage loans, GDP per capita, and inflation rate. The research results reveal that Ukrainian migration has a significant positive impact on the real estate market, leading to price increases for housing in urban areas and increased demand for rental housing. In addition, mortgage interest rates show a significant negative impact, suggesting that lower affordability of financing limits purchases of real estate. Moreover, GDP growth per capita is positively correlated with price dynamics in the real estate market, confirming that a prosperous economy stimulates investments in real estate. Findings provide valuable insights into understanding how geopolitical and economic factors interact to influence the real estate market.